Gracing Neuroscientific Tendencies of the Embodied Soul - Graves, Mark (Philosophy & theology, 2014)
Advances in scientific study of the brain now enable the examination of nature and grace in human rationality’s embodiment in the brain’s biological processing. I model the brain’s biology using the dispositional tendencies of nature—characterized by Jonathan Edwards, C. S. Peirce, and the Jesuit philosophical theologian Donald Gelpi—to examine gracing of the mind’s habit formation (habitus) in terms of memory, learning, and decision making. This turn to tendency suggests a shift from understanding soul as Aristotelian act to instead emphasizing the potentiality informing the body and clarifies a scientifically plausible Rahnerian interpretation of obediential potency.